Emerging uses of circulating tumor DNA in advanced stage nonsmall cell lung cancer - Marmarelis, Melina; Thompson, Jeffrey C.; Aggarwal, Charu; Evans, Tracey L.; Carpenter, VErica; Cohen, Roger B.; Langer, Corey J.; Bauml, Joshua (Annals of Translational Medicine, 2017)
Targeted therapies have dramatically changed the treatment paradigm for a select group of patients with non-small cell lung cancer (NSCLC) whose tumors harbor targetable genetic aberrations. Patients with such genetic changes enjoy excellent responses to tyrosine kinase inhibitors (TKIs), but resistance is nearly inevitable. Resistance to first line TKIs is heterogeneous and multifactorial—multiple resistance mechanisms have been reported, and different metastatic foci in the same patient may have distinct resistance mechanisms. The recent approval of next-generation TKIs specific to particular resistance mechanisms, and the likely future approval of others, necessitates the acquisition of repeat molecular analysis at time of progression. Tumor tissue has traditionally been the preferred source to detect oncogenic driver and resistance mutations, but tissue biopsies are invasive and often difficult to obtain. The use of circulating tumor DNA (ctDNA), so-called “liquid biopsies”, has emerged as a promising technique to molecularly profile tumors non-invasively and is becoming increasingly utilized in the routine management of lung cancer. This review will describe the current role of ctDNA in the management of lung cancer, and explore emerging data that point towards its increasingly important role in clinical care.